Analisis Kecurangan pada Laporan Keuangan dengan Metode Fraud Hexagon dan Kepemilikan Institusional sebagai Variabel Moderasi (International Forum of Researchers and Lecturers, 2025)
This study examines in depth the risk factors influencing financial statement fraud in the Indonesian banking sector by employing the Fraud Hexagon framework. This framework comprises six core elements—pressure, opportunity, rationalization, capability, arrogance, and collusion—each representing potential drivers of fraudulent behavior. The study also aims to assess whether institutional investor involvement can serve as a moderating factor capable of reducing the likelihood of fraud. The research uses secondary data derived from the annual reports of banks listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023. Logistic regression analysis is employed to examine the relationships between the Fraud Hexagon variables and financial statement fraud, as well as to test the moderating role of institutional ownership. The findings reveal that, among the six elements of the Fraud Hexagon, only auditor changes (representing rationalization) and political connections (representing collusion) have a significant effect on financial statement fraud. The other elements—pressure, opportunity, capability, and arrogance—do not show a significant impact. Furthermore, institutional investor involvement is found not to moderate the relationship between the Fraud Hexagon elements and financial statement fraud, indicating that external monitoring through institutional ownership remains ineffective in the context of Indonesian banking. These results underscore the importance of closer supervision of rationalization and collusion factors, as well as the need for stronger internal control mechanisms to prevent fraudulent financial reporting. The study’s findings are expected to provide valuable insights for regulators, banking management, and other stakeholders in their efforts to enhance fraud prevention measures in the financial sector.